NAVIGATING “SAFETY” IN A PANDEMIC: A CRITICAL EXAMINATION OF ONTARIO CHILD WELFARE SAFETY INTERVENTIONS FOR NEWCOMER PARENTS AND OTHER FAMILIES DURING THE COVID-19 PANDEMIC - Kikulwe, Daniel; Maiter, Sarah (International Journal of Child, Youth and Family Studies, 2024)
This study investigated circumstances surrounding the impact of COVID-19 on child protection investigations, particularly those affecting newcomer parents in Ontario, Canada. Recognizing that the pandemic inflicted substantial socioeconomic disadvantage on some people, the purpose of the study was to use an intersectional lens to examine challenges and solutions found by child welfare agencies when working with families. Insights for policy and practice are drawn from 11 virtual interviews with child welfare workers and managers in Ontario. Our findings reveal that some newcomer families encountered unique challenges: ineligibility for the available pandemic public assistance; inaccessibility to faith-based supports, which had often been their first key contact for mental wellness in the past; technological inequities; and language barriers. These intersecting conditions impacted newcomer families and led to innovative child protection interventions. Analysis of the interview data shows a gradual shift in Ontario from risk-focused approaches to supportive and preventative child welfare interventions in families. Furthermore, supervisors faced the dilemma of how stringently to enforce ongoing safety policies when some social workers were questioning the benefits of these rules for families with intersecting identities who were experiencing added burdens because of the pandemic.